2018
DOI: 10.1111/pai.12974
|View full text |Cite
|
Sign up to set email alerts
|

Egg oral immunotherapy in children (SEICAP I): Daily or weekly desensitization pattern

Abstract: PEW OIT is an effective treatment for children with persistent egg allergy. A 30% weekly plus 5% daily increment pattern could be more effective and safer than one with only 30% weekly increments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 25 publications
2
44
0
Order By: Relevance
“…The primary sources of data were peer-reviewed full-text publications retrieved through searching multiple sources, including PubMed, MEDLINE (Ovid), Embase, EBM Reviews, CINAHL and Web of Science bibliographic databases. Searches for OIT clinical data were performed on April 17-18, 2019, and searches for epidemiological and burden of disease data were performed on May [30][31]2019. Search terms are presented in Additional file 1: Appendix 2A.…”
Section: Literature Review Sources Of Datamentioning
confidence: 99%
See 3 more Smart Citations
“…The primary sources of data were peer-reviewed full-text publications retrieved through searching multiple sources, including PubMed, MEDLINE (Ovid), Embase, EBM Reviews, CINAHL and Web of Science bibliographic databases. Searches for OIT clinical data were performed on April 17-18, 2019, and searches for epidemiological and burden of disease data were performed on May [30][31]2019. Search terms are presented in Additional file 1: Appendix 2A.…”
Section: Literature Review Sources Of Datamentioning
confidence: 99%
“…There is no convincing evidence of a clinically significant difference between food allergens in terms of safety and efficacy outcomes in OIT for the treatment of IgEmediated food allergy. Therefore, all recommendations in these CPGs are generally applicable to all food allergens, unless there is specific evidence to demonstrate otherwise This recommendation is based on the principle of equity of eligibility It is supported by large amount of consistent clinical evidence, considering the absence of demonstrated lack of efficacy or of a consistent safety issue for any specific food despite a large number of clinical studies for a variety of foods [22][23][24][29][30][31][32][33][34][35][36][37][38]. Level of evidence: HIGH It is also supported by the lack of biological plausibility that the mechanism of OIT would differ from one allergen to another.…”
Section: Ethical Imperative Data or Other Considerations In Support mentioning
confidence: 99%
See 2 more Smart Citations
“…144 A Spanish study of 101 children with egg allergy randomized to faster (dose increase of 30% weekly plus 5% daily) or slower (30% weekly) concluded that the faster group was more likely to reach maintenance (96.15% vs 75.80%) and had fewer allergic reactions. 145 The target or maintenance dose of OIT varied greatly in studies and affects the goal outcome of OIT, that is, introduction into the diet vs protection from cross-contamination. 146,147 Lower doses appear easier to achieve and may be more efficacious.…”
Section: Clinic Al Mark Er S and Pro Cedur Al Fac Tor S Of Tre Atmementioning
confidence: 99%